Domestic Violence Legislation in Greece: Analysis of Penal Mediation - Ranjan, Sheetal (Women & criminal justice, 2020)
This article presents an analysis of the penal mediation clause within Greece’s domestic violence legislation (Law 3500/2006) in the context of contemporary criminal justice theories. An overview of Law 3500/2006 will be presented, along with highlights of recent changes leading to Law 4531/2018 ratified as part of the Istanbul Convention and Law 4604/2019 designed to enhance gender equality. The penal mediation component of the Law will be discussed in depth and theories related to application of coordinated community response, restorative justice, and power and control will be highlighted. Current debates that lack clarity and scientific evidence, and could possibly lead to dismantling a “good” legal provision, will be presented. Greece’s penal mediation provision has the potential to be a best practice. However, lacking a proper evaluation, this information could be prematurely lost. Last, an action plan for scientific evaluation and legal clarification of the penal mediation clause will be presented.